Model Kepemimpinan Transformasinal Kepala Sekolah SMK Negeri - Sitti Hartinah (Jurnal Pendidikan dan Kebudayaan, 2011)
The ground reasons of this study is in what way transformational leadership is suitable toÂ increase education quality in vocational high school. Meanwhile, the specific problems are as follows: (1)Â do principalsâ€™ competency variables consisting of personality, management, entrepreneurship, supervision,Â and social competency dimensions directly contribute and significantly influence to the principalsÂ transformational leadership?; (2) do school organizational conditions to directly contribute and significantlyÂ influence to the principals transformational leadership?; (3) do work ethics contribute and significantlyÂ influence to the principals transformasional leadership?; and (4) in what way is principals transformationalÂ leadership model suitable to increase education quality of vocational high schoolsâ€™ principals. This research design was confirmatory factor analysis approach was Structural Equation Model (SEM). TheÂ result of this study shows that school principal competence contributes (24,5%) and significantly influencesÂ to school principal leadership, school organizational conditions (29,4%) and significantly influences toÂ principal transformational leadership, meanwhile the determinant factors including school principalÂ competence, school organizational conditions and work ethics contribute (0,856%) and significantlyÂ influence. A suitable principal transformational leadership model to develop vocational high school qualityÂ is through school organizational conditions; work ethics; principal competence rights. Based on these findings, a school principal should be guided by the main principle when he performsÂ his work, in order to have abilities and skills in managing his school effevtively; a principal should haveÂ work-culture to achieve an effective school organizational conditions; a principal should be able toÂ increase a culture of work ethics for school members by enhancing their presence to always come atÂ school; has commitment to develop his school, educational institutions should arrange the planning ofÂ principals training about soft skill entrepreneurship in order they have maximal work ethics in increasingÂ the education quality at vocational high school.ABSTRAKModel kepemimpinan transformasional kepala sekolah terbentuk dari berbagai asfek yaitu kompetensi, iklim organisasi sekolah dan etos kerja.Permasalahannya adalah apakah model kepemimpinan transformasional kepala sekolah dikonstruk dari dimensi kompetensi, iklim organisasi sekolah dan etos kerja. Tujuan penelitian ini mencari model kepemimpinan transformasional kepala sekolah di SMKN Tegal. Desain penelitian ini adalah berpendekatan confirmatory factor analysis. Jumlah sampel 200 dipilih secara proportional random sampling. Instrumen menggunakan â€œquestionareâ€dengan reliability. Desain penelitian dengan paradigma kuantitatif, menjelaskan hubungan kausal variabel melalui uji hipotesis, dengan pemodelan persamaan structural (SEM). Hasil analisis menemukan kesesuaian model konseptual dengan model teruji bahwa kepemimpinan transformasional kepala sekolah dipengaruhi secara signifikan oleh; kompetensi kepala sekolah (24,5%); iklim organisasi sekolah (29,4%); etos kerja (28,1%); Model faktor kompetensi kepala sekolah, iklim organisasi sekolah, dan etos kerja secara simultan berkontribusi terhadap kepemimpinan transformasional kepala sekolah sebesar (85,6%). Implikasinya jika ingin meningkatkan kompetensi kepala sekolah, iklim organisasi sekolah dan etos kerja maka perlu dikembangkan model kepemimpinan transformasional kepala sekolah dalam model yang teruji ini. Berdasarkan temuan, disarankan agar kepala sekolah, memiliki keterampilan manajerial, memperbaiki iklim organisasi sekolah dan peningkatan etos kerja kepala secara maksimal